PENGELOLAAN BERKELANJUTAN EKOWISATA HUTAN LARANGAN ADAT KENEGERIAN RUMBIO - Atika Azharo; Suwondo .; Ridwan Manda Putra (JURNAL ILMU-ILMU KEHUTANAN, 2020)
This study aims to determine the sustainability status of the Kenegerian Rumbio Indigenous Forest Management ecotourism. The type of data collected includes primary data and secondary data. Data was collected using survey methods, interviews and literature. The method used in this research is Multidimesional Scalling (MDS) analysis. Sustainability analysis is carried out using the MDS analysis approach with the help of Rap-InsusEco software. The sustainability status of managing the Kenegerian Rumbio Indigenous Forest Ecotourism Forest is currently multidimensional in the category of quite sustainable. The results of the analysis of each dimension are the ecological dimension (72.5%) the economic dimension (33.4%) and the socio-cultural dimension (51.6%). The design of sustainable ecotourism management in the Kenegrian Rumbio Indigenous Forests by: (1) Establishment of clear ecotourism planning and management (2) Safeguarding and monitoring forest access (3) Establishment of business partners (4) Means of ecotourism information on Kenegerian Rumbio Indigenous Forests (5) Determination of ideas and ideas for the formation of attractions (6) Support from various parties (7) Financial support, infrastructure and mental readiness of the community.